Gendered patterns of time use over the life cycle: Evidence from Turkey - Ebru Kongar; Emel Memiðs (Levy Economics Institute of Bard College, 2017)
Using data from the 2006 Turkish Time-Use Survey, we examine gender differences in time allocation among married heterosexual couples over the life cycle. While we find large discrepancies in the gender division of both paid and unpaid work at each life stage, the gender gap in paid and unpaid work is largest among parents of infants compared to parents of older children and couples without children. The gender gap narrows as children grow up and parents age. Married women's housework time remains relatively unchanged across their life cycle, while older men spend more time doing housework than their younger counterparts. Over the course of the life cycle, women's total work burden increases relative to men's. Placing our findings within the gendered institutional context in Turkey, we argue that gender-inequitable work-family reconciliation policies that are based on gendered assumptions of women's role as caregivers exacerbate gender disparities in time use.
Keywords: D13; J16; J22; 330; Economics of Gender; Time Use; Life Cycle; Turkey